Charcot–Marie–Tooth disease type 1A: Longitudinal change in nerve ultrasound parameters. Issue 6 (27th September 2020) - Kojima, Yuta; Noto, Yu‐ichi; Tsuji, Yukiko; Kitani‐Morii, Fukiko; Shiga, Kensuke; Mizuno, Toshiki; Nakagawa, Masanori
Abstract: Background: This study aimed to elucidate the longitudinal changes in nerve ultrasound parameters of adult Charcot–Marie–Tooth disease type 1A (CMT1A) patients. Methods: Fifteen adult patients with CMT1A prospectively underwent nerve ultrasound and clinical assessment (CMT neuropathy score [CMTNS]) at baseline and 5 y later. Nerve cross‐sectional area (CSA) and echogenicity were measured in the median and sural nerves. Changes in ultrasound parameters and CMTNS and correlation between changes of ultrasound parameters and CMTNS were analyzed. Results: Median and sural nerve CSAs did not change over 5 y, although CMTNS increased ( P < .01). Nerve echogenicity in the sural nerve decreased over 5 y ( P = .045). No correlations between changes in nerve ultrasound parameters and CMTNS were identified. Conclusions: No longitudinal changes in nerve size was detected in adult CMT1A. Exploring the factors that determine nerve size in childhood CMT1A may lead to the development of treatments.